Improvement of iron content, total phenolic, and antioxidant activity of green spinach (Amaranthus tricolor L.) with maggot fertilizer - Andrianto, Dimas; Nurcholis, Waras; Ghifari, Muhammad Nabil (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Green spinach (Amaranthus tricolor L.) is a plant that contains various vitamins, such as vitamins A, B, and C, as well as protein and fiber. Green spinach contains high iron. Besides that, spinach also contains secondary metabolites such as flavonoids, antioxidants, and phenolics, which are beneficial for degradative diseases. This study aimed to evaluate the impact of plant height, iron content, total phenolic content, and antioxidant activity in spinach plants using a 70% ethanol solvent. The samples were extracted through a maceration method in a microwave for 3 minutes, followed by filtration to obtain the test sample filtrate. Iron content was determined using the ICP-OES method, total phenolic content (TPC) was measured with the Folin-Ciocalteu method, and antioxidant activity was assessed using the DPPH method. The findings revealed that treatment 2 (2 parts maggot fertilizer to 8 parts soil) had the highest iron content and antioxidant activity, whereas treatment 1 (1 part maggot fertilizer to 9 parts soil) showed the greatest plant growth and phenolic content. Keywords: allelochemical; bioherbicide; inhibitory effect; weed control